Analisis Pengaruh Self-Efficacy dan Motivasi Kerja terhadap Disiplin Kerja dan Kinerja Karyawan: Tinjauan Sistematik Kajian - Didin Sjarifudin; Hibarkah Kurnia; Erwin Barita Maniur Tambunan (Program Studi Teknik Industri, Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2023)
An organization wants its business journey to run smoothly, but sometimes there are obstacles from the different nature of employees. The great influence of employee character starts from self-efficacy, work motivation, work discipline and employee performance. The purpose of this research is to build a research hypothesis on the influence of exogenous variables, namely self-efficacy and work motivation on the endogenous variables of work discipline and employee performance. This research method uses Systematic Literature Review (SLR) with secondary data taken from several collections of articles related to these variables. This study has found that there is a positive mutually influencing relationship between variables, among which self-efficacy influences work discipline, work motivation influences work discipline, self-efficacy influences employee performance, work motivation influences employee performance, and work discipline influences on employee performance. This research has resulted in several studies of 10 articles which have provided scientific decisions. The contribution of this research is expected to provide convenience for other researchers who will develop their scientific work with a similar theme in the future.